Endoscopic diagnosis and treatment of biliary complications after orthotopic liver transplantation - A. V. Kurenkov; M. S. Novruzbekov; K. M. Magomedov; S. V. Shvarts; YU. S. Teterin; A. V. Mironov; O. D. Olisov (Трансплантология (Москва), 2018)
Aim. The aim of the study was to investigate the endoscopic diagnostic and treatment techniques for biliary complications after orthotopic liver transplantation, their efficacy and safety. Material and methods. The study was based on the results of endoscopic treatment of 29 patients with biliary complications occurred after orthotopic liver transplantation in N.V. Sklifosovsky Research Institute for Emergency Medicine in the period from December 2001 to January 2017. Conclusions. The state-of-the-art methods of therapeutic endoscopy enable a successful treatment of most cases of biliary strictures and biliary-biliary anastomosis incompetence, thus achieving good long-term results using a minimally invasive methodology.